Longitudinal Impact of Depressive Symptoms and Peer Tobacco Use on the Number of Tobacco Products Used by Young Adults - Caroline North (MDPI AG, 2021)
We examined the role of depressive symptoms in the longitudinal trajectory of the number of tobacco products used across young adulthood, ages 18–30 years, and whether peer tobacco use exacerbated the effects of the depressive symptoms. Participants were 4534 initially 18–25-year-old young adults in the Marketing and Promotions Across Colleges in Texas project (Project M-PACT), which collected data across a 4.5-year period from 2014 to 2019. Growth curve modeling within an accelerated design was used to test study hypotheses. Elevated depressive symptoms were associated with a greater number of tobacco products used concurrently and at least six months later. The number of tobacco-using peers moderated the association between depressive symptoms and the number of tobacco products trajectory. Young adults with elevated depressive symptoms used a greater number of tobacco products but only when they had a greater number of tobacco-using peers. Findings indicate that not all young adults with depressive symptoms use tobacco. Having a greater number of tobacco-using peers may facilitate a context that both models and encourages tobacco use. Therefore, tobacco prevention programs should aim to include peer components, especially for young adults.